2014
DOI: 10.1080/08927014.2014.972951
|View full text |Cite
|
Sign up to set email alerts
|

Long-term microfouling on commercial biocidal fouling control coatings

Abstract: The current study investigated the microbial community composition of the biofilms that developed on 11 commercial biocidal coatings, including examples of the three main historic types, namely self-polishing copolymer (SPC), self-polishing hybrid (SPH) and controlled depletion polymer (CDP), after immersion in the sea for one year. The total wet weight of the biofilm and the total bacterial density were significantly influenced by all coatings. Pyrosequencing of 16S rRNA genes revealed distinct bacterial comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 53 publications
13
57
2
Order By: Relevance
“…Our results indicated that the amount of bacteria on the surfaces from the control system was 10 8 cells·cm −2 . Similar numbers of bacterial microfouling have been reported on anti-fouling surfaces in oceanic waters, also in much warmer sites [24][25][26]. Hypochlorite treatment reduced the bacterial numbers by 10-1000-fold, but the efficiency depended on the coating.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Our results indicated that the amount of bacteria on the surfaces from the control system was 10 8 cells·cm −2 . Similar numbers of bacterial microfouling have been reported on anti-fouling surfaces in oceanic waters, also in much warmer sites [24][25][26]. Hypochlorite treatment reduced the bacterial numbers by 10-1000-fold, but the efficiency depended on the coating.…”
Section: Discussionsupporting
confidence: 49%
“…Here, the anti-fouling coatings alone did not prevent the settlement of microfouling organisms. Since microbial fouling affects the performance of commercial antifouling coatings the quantitative and qualitative analyses of marine microbial fouling communities is of great interest [25,39]. As summarized by Flemming [4], detailed knowledge about biofilms is crucial for understanding and preventing biofouling, as well as to choose a successful anti-fouling strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria that contributed less than 1% are not shown. formation of fouling communities are largely unknown (Salta et al 2013;Ling et al 2014;Muthukrishnan et al 2014). The current investigation revealed that the incorporation of the CNTs and TiO 2 nanoparticles into PDMS coatings impacted the formation of microbial biofilms, which subsequently reduced mussel plantigrade settlement.…”
Section: Settlement Assaymentioning
confidence: 94%
“…This frequency of hull cleaning is insufficient to reduce the risk of invasive species and may leave settlement cues from macrofouling organisms that influence subsequent settlement (Ralston & Swain 2014). It has also been shown that the nature and quantity of biofilms present differs among the types of antifouling (AF) coatings (Zargiel et al 2011;Hunsucker et al 2014;Muthukrishnan et al 2014;Zargiel & Swain 2014). Specifically, the age, composition, and thickness of a biofilm have been shown to influence the organisms that subsequently settle on a coated surface as well as their adhesion and growth properties (Dobretsov et al 2013;Mieszkin et al 2013;Shikuma et al 2014).…”
Section: Introductionmentioning
confidence: 96%